Effect of gibberellic acid on Malaysia cytoplasmic male sterile line during hybrid rice seed multiplication - Hashim, Shahida; Ding, Phebe; Fadzli, Muhammad Naim (Asian Network for Scientific Information, 2023)
Background and Objective: Poor cross-pollination or out-crossing between parental lines is the major constraint in hybrid rice seed production. One of the reasons is due to poor panicle exertion of the cytoplasmic male sterile (CMS) line. The aim of this study was to improve the out-crossing rate and grain yield during CMS seed multiplication. Materials and Methods: The study was conducted at the Centre of Excellent for Rice, MARDI Seberang Perai, Penang, Malaysia using a randomized complete block design with 3 replications. Four concentrations of gibberellic acid (GA3) were applied to both 0047A CMS and 0047B maintainer lines when 10% of the panicles emerged out from the sheath. Results: The result showed that the application of GA3 had significantly affected the plant height, panicle exsertion rate, seed setting, grain yield and harvest index of 0047A CMS. The internode of 0047A CMS also showed some similarities and variations between the untreated and treated plants (the CMS was applied with and 30 mg L–1 GA3). Conclusion: The application of GA3 at the concentration of 15 and 30 mg L–1 is recommended to improve the panicle exertion of 0047A CMS during CMS seed multiplication.